Naringenin suppresses BEAS-2B-derived extracellular vesicular cargoes disorder caused by cigarette smoke extract thereby inhibiting M1 macrophage polarization - Chen, Zhen; Wu, Hao; Fan, Weiyang; Zhang, Jiashuo; Yao, Yue; Su, Weiwei; Wang, Yonggang; Li, Peibo (Frontiers in Immunology, 2022)
Exosome-mediated epithelium-macrophage crosstalk has been proved to maintain lung homeostasis in cigarette smoke-induced lung diseases such as COPD. In our previous study, we found that exosomes derived from cigarette smoke extract (CSE) treated BEAS-2B promoted M1 macrophage polarization, which probably accelerated the development of inflammatory responses. Naringenin has been proved to suppress M1 macrophage polarization, but whether naringenin regulates macrophage polarization mediated by exosomes has not been reported. In this study, we firstly found that exosomes derived from naringenin and CSE co-treated BEAS-2B significantly inhibited the expression of CD86 and CD80 and the secretion of TNF- α, IL-6, IL-1 β, iNOS, and IL-12 in macrophage induced by exosomes derived from CSE-treated BEAS-2B. Further research revealed that naringenin downregulated BEAS-2B-derived exosomal miR-21-3p which targeted PTEN/PI3K/AKT cascade in macrophages and then suppressed M1 macrophage polarization. Subsequent exosomal proteomics suggested that naringenin decreased BEAS-2B-derived exosomal PARP1 expression thereby suppressing M1 macrophage polarization probably. Our study provides novel pharmacological references for the mechanism of naringenin in the treatment of cigarette smoke-induced lung inflammatory diseases.